Boron‐Catalyzed Graphitization Carbon Layer Enabling LiMn0.8Fe0.2PO4 Cathode Superior Kinetics and Li‐Storage Properties. Issue 2 (21st December 2022) - Zeng, Taotao; Hu, Zhuang; Zhou, Zeyan; Fan, Changling; Zhang, Fuquan; Liu, Jinshui; Liu, Dai‐Huo
Abstract: The poor electrode kinetics and low conductivity of the LiMn0.8 Fe0.2 PO4 cathode seriously impede its practical application. Here, an effective strategy of boron‐catalyzed graphitization carbon coating layer is proposed to stabilize the nanostructure and improve the kinetic properties and Li‐storage capability of LiMn0.8 Fe0.2 PO4 nanocrystals for rechargeable lithium‐ion batteries. The graphite‐like BC3 is derived from B‐catalyzed graphitization coating layers, which can not only effectively maintain the dynamic stability of the LiMn0.8 Fe0.2 PO4 nanostructure during cycling, but also plays an important role in enhancing the conductivity and Li + migration kinetics of LiMn0.8 Fe0.2 PO4 @B‐C. The optimized LiMn0.8 Fe0.2 PO4 @B‐C exhibits the fastest intercalation/deintercalation kinetics, highest electrical conductivity (8.41 × 10 −2 S cm −1 ), Li + diffusion coefficient (6.17 × 10 −12 cm 2 s −1 ), and Li‐storage performance among three comparison samples (B‐C0, B‐C6, and B‐C9). The highly reversible properties and structural stability of LiMn0.8 Fe0.2 PO4 @B‐C are further proved by operando XRD analysis. The B‐catalyzed graphitization carbon coating strategy is expected to be an effective pathway to overcome the inherent drawbacks of the high‐energy density LiMn0.8 Fe0.2 PO4 cathode and to improve other cathode materials with low‐conductivity and poor electrode kinetics for rechargeable second batteries. Abstract : A boron‐catalyzed graphitization carbon coating strategy is proposed to boost the ionic/electronic kinetics behaviors and Li‐storage capabilities of the high‐energy LiMn0.8 Fe0.2 PO4 cathode. The highly reversible phase transition mechanisms and superior structural stability of LiMn0.8 Fe0.2 PO4 @B‐C are illustrated via operando XRD testing. Hence, the LiMn0.8 Fe0.2 PO4 @B‐C cathode exhibits outstanding rate capability and cycling stability in lithium‐ion batteries.